The Development of the Brewing Industry in South Bohemian Region in The Turn Of The 20th And 21st Centuries - Stellner, František; Polánecký, Lukáš (KVASNY PRUMYSL, 2016)
The study showed that the South Bohemian beer industry is developing in a specific way within the Czech beer production. Only in the South Bohemian region during the small privatization, sales of two major breweries were implemented. The only privatized brewery in the Czech republic that is town property, the Strakonice Brewery, is located in the South Bohemian region. Another distinction is that only the Budweiser Budvar Brewery has not been privatized until this day and is the only and last state enterprise. Also very specific is the fact that the Budweiser Budvar is only fourth place in beer production but first in beer export in the Czech republic.